Efecto de la rinitis y el asma en el ausentismo y rendimiento laboral y escolar en una población del trópico latinoamericano (2016)
ABSTRACT: Background: Asthma and rhinitis are the most frequent chronic respiratory diseases. Their high impact is associated with the loss of working days, as well as a decrease in academic performance. Objective: To assess and compare the impact of rhinitis and asthma as causes of absenteeism and low work performance in a population of children and adults. Material and method: A cross sectional study was performed in 10 schools of two cities in Colombia. The student population between 6 to 17 years, as well as the faculty staff over 18 were invited to participate. All of the participants filled a questionnaire assessing parameters related to clinical background, and a review of scores in Math and Spanish, curriculum vitae and number of missed day during the last academic period completed was performed. Results: A total of 1,413 participants were enrolled. The frequency of asthma and/or rhinitis was 36%, there was a greater frequency of absenteeism in the population of children with respiratory symptoms (2.8 vs 1.2 days/year/patient, p<0.01) and there was both a lower academic (failure in 17% vs 9%, p<0.05) and work performance (0.43 vs 0.27, p<0.05) in the symptomatic population. We observed that those patients with good adherence to pharmacologic treatment displayed lower absenteeism and an improved performance. Conclusion: Both rhinitis and asthma are associated with lower performance in children and adults and absenteeism in the school; however, adequate treatment may improve clinical control and reduce backlash against job performance.